2020
DOI: 10.3390/nano10112277
|View full text |Cite
|
Sign up to set email alerts
|

Novel Benchtop Magnetic Particle Spectrometer for Process Monitoring of Magnetic Nanoparticle Synthesis

Abstract: Magnetic nanoparticles combine unique magnetic properties that can be used in a variety of biomedical applications for therapy and diagnostics. These applications place high demands on the magnetic properties of nanoparticles. Thus, research, development, and quality assurance of magnetic nanoparticles requires powerful analytical methods that are capable of detecting relevant structural and, above all, magnetic parameters. By directly coupling nanoparticle synthesis with magnetic detectors, relevant nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Despite working with highest precision, potential inaccuracies while pipetting increase with a diminishing total iron amount. We evaluate the absolute values of the third harmonic of the measured magnetization response in the frequency domain (Löwa et al 2020) to compare the results of the 4 different MNPs.…”
Section: Serial Dilutionmentioning
confidence: 99%
“…Despite working with highest precision, potential inaccuracies while pipetting increase with a diminishing total iron amount. We evaluate the absolute values of the third harmonic of the measured magnetization response in the frequency domain (Löwa et al 2020) to compare the results of the 4 different MNPs.…”
Section: Serial Dilutionmentioning
confidence: 99%
“…Coating (for example by poly-l-lysine) to obtain stable nonpyrogenic MNP suspension [115] product homogeneity quality reduction by concentration gradients and hot spots in the reaction flask [25,51] enhanced quality due to homogeneous morphology, narrow size distribution [25,67,116] high within one bacteria strain but strain variation possible [52][53][54]95] reproducibility, production rate and scale-up capability significant batch to batch variations in size, morphology, and magnetic properties [25,111,[117][118][119], poor scaling up capability. A reported study from Lin et al showed a production rate of 4.73 g/h for microfluidic synthesis comparing to 1.4 g/h for conventional synthesis with the same conditions [89] continuous production, no batch-to-batch variation, high scale-up capability high at the defined environmental conditions [92], mg/(L • day) production rate [52], high scale-up capability, though challenging due to long term bacteriostatic growth conditions [38,40,46,78] clogging not applicable microchannel-wall blocking during nucleation or by agglomeration [77,104,[120][121][122] not applicable automation poor feasible/integratable [66,123,124] capability of online characterization not applicable for batch, though magnetic characterization of whole batches by magnetic particle spectroscopy is feasible parameter control and synthesis adjustment feasible during synthesis, control of magnetic parameters by magnetic particle spectroscopy [25,125] and NMR [126] cost low, common lab equipment expensive microreactor fabrication expensive specialized equipment…”
Section: Comparison Of Different Synthesesmentioning
confidence: 99%
“…Online-MPS measurements were performed using a novel benchtop magnetic particle spectrometer with an integrated flow cell so that it could be connected directly to the growth stage of the micromixer platform. This device was recently developed at Physikalisch-Technische Bundesanstalt and is described in detail in [57]. It operates at the same basic frequency of 25 kHz as the commercial MPS device and is calibrated using reference samples measured with the calibrated commercial MPS device before.…”
Section: Magnetic Particle Spectroscopy (Mps)mentioning
confidence: 99%